Synergism of Azadirachta indica A. Juss. and Piper sarmentosum Roxb. emulsion formulation against Nilaparvata lugens (Stål.) - Mawi, Masdah (2022)
Nilaparvata lugens, brown planthopper is an important rice pest that destroys rice by feeding on the plant sap and causing a condition known as ‘hopper burn’, where the plants are completely wilted, yellow and dried. The constant use of chemical substances had built the resistance of pests toward chemical insecticide. As an alternative, a more environmentally-friendly approach such as the use of biopesticide should be implemented. Biopesticide formulation which combined more than one active ingredient to produce joint toxicity effect has gaining attention lately for its effectiveness. Thus, this study aims to determine the synergism effect of Piper sarmentosum and Azadirachta indica against N. lugens. Piper sarmentosum is a common herb used in cooking while A. indica is known for its medicinal properties. Bioassay of the extracts against N. lugens nymphs showed a synergistic effect from treatments T6, T7 and T9, with mixture ratio of P. sarmentosum to A. indica at 6:4, 7:3 and 9:1. T9 caused highest nymph mortality after 72 hours treatment. Emulsion formulations were developed by mixing 5 % extracts combination from T6, T7 and T9 with 14.25 % carrier oil (Edenor), 76 % surfactant (Tween 80 and Termul 1284), and 4.75 % water. Six formulations coded as F1, F2, F3, F4, F5 and F6 had been developed. Characterization, including stability, particle size, zeta potential, PDI value, pH, and viscosity analysis, resulted in ideal nano emulsion size ranged from 202.5 to 635.9 nm. Stability and thermostability tests that were performed and successfully produced stable and homogenous nano emulsion. F4 can be selected as the best formulation because it has the best zeta potential (-65.0 mV) and viscosity value (67.2 mPa/s), the size is in nano emulsion size range (415.3 nm), remained homogenous for centrifugation and stability test, PDI value indicated it is in ideal monodisperse phase (0.418), low surface tension (35.2 mN/m) and low pH (4.0). The formulations were then used in nymph mortality bioassay test on third instar N. lugens nymphs to evaluate the formulation's efficacy against N. lugens. The lethal concentration, LC50 and sub lethal, LC10 and LC25 were determined from bioassay. LC50 can control at least half of the treated population, while LC10 and LC25 can control 10% and 25% of population. Highest mortality can be seen on F2 (0.043 mg/l) and the lowest was F5 (0.117 mg/l). The value of lethal and sub lethal concentration were used in a test against female N. lugens to determine the effect of formulations on fecundity of N. lugens. There are significant differences on the number of eggs produced after treatments. F4 at LC50 was found to cause most effective effect as it produced the least number of eggs produced, 114 eggs. In conclusion, stable formulation can be developed following the current results and findings. These will lead to the synergism efficacy of A. indica and P. sarmentosum against N. lugens through emulsion formulations as joint toxicity could have a better potency in controlling pests, compared to individual active ingredient.